Feasibility of Intraoperative Normothermic Intraperitoneal Chemotherapy Following Optimal Cytoreduction in Advanced Ovarian Carcinoma: A Pilot Study - Baruah, Upasana; Roy, Partha Sarathi; Barmon, Debabrata (Asian Pacific Journal of Cancer Care, 2024)
Introduction: Based on the results of studies using HIPEC, EPIC, and normothermic intraperitoneal chemotherapy, we hypothesized that the instillation of normothermic chemotherapy after optimal cytoreduction would improve survival in patients undergoing this procedure. To test this hypothesis, we conducted a feasibility study to evaluate the effectiveness of intraoperative normothermic intraperitoneal chemotherapy in patients with advanced-stage epithelial ovarian carcinoma. Methods: This single institutional feasibility study aimed to assess the primary objective of progression-free survival (PFS) following the instillation of normothermic chemotherapy after optimal cytoreduction in cases of advanced ovarian cancer following neoadjuvant chemotherapy. The secondary objective was to evaluate tolerability and toxicity. The study received clearance from the institutional ethical committee. Results: A total of 24 patients were included in the pilot study, which spanned two years. Short-term analysis was conducted by comparing these patients with a group of 45 individuals who underwent interval cytoreductive surgery (ICS) with CC 0 and 1 during the same period. The most common side effect observed was prolonged post-operative ileus, which occurred in six patients. The median PFS among patients who received intraperitoneal (IP) chemotherapy was significantly longer compared to patients who received ICS alone (34.0 vs. 13.0 months, p=0.018). Conclusion: Due to global resource limitations, the implementation of uniform state- of-the-art management for advanced epithelial ovarian cancer may not be accessible to all patients. Although the evidence is limited by the small sample size and short follow-up duration, the findings of this feasibility study are encouraging. The study provides substantial evidence to support further exploration of this approach within our institute and to plan a randomized controlled trial to gather more conclusive evidence.